2021
DOI: 10.3390/rs13050863
|View full text |Cite
|
Sign up to set email alerts
|

Signal Photon Extraction Method for Weak Beam Data of ICESat-2 Using Information Provided by Strong Beam Data in Mountainous Areas

Abstract: The Ice, Cloud, and land Elevation Satellite-2 (ICESat-2) can measure the elevations of the Earth’s surface using a sampling strategy with unprecedented spatial detail. In the daytime of mountainous areas where the signal–noise ratio (SNR) of weak beam data is very low, current algorithms do not always perform well on extracting signal photons from weak beam data (i.e., many signal photons were missed). This paper proposes an effective algorithm to extract signal photons from the weak beam data of ICESat-2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The ICESat-2 carries an advanced terrain laser altimeter system (ATLAS), which emits three pairs of beams. The distance between each pair of beams is about 3.3 km, and the distance between two trajectories in the beam is 90 m. Three pairs of laser beams represent six ground trajectories, and the corresponding data numbers from left to right are, respectively, Ground Track 1 Left (GT1L) to Ground Track 3 Right (GT3R) [14,19,47,48].…”
Section: Icesat-2 Atlas Data and Processingmentioning
confidence: 99%
“…The ICESat-2 carries an advanced terrain laser altimeter system (ATLAS), which emits three pairs of beams. The distance between each pair of beams is about 3.3 km, and the distance between two trajectories in the beam is 90 m. Three pairs of laser beams represent six ground trajectories, and the corresponding data numbers from left to right are, respectively, Ground Track 1 Left (GT1L) to Ground Track 3 Right (GT3R) [14,19,47,48].…”
Section: Icesat-2 Atlas Data and Processingmentioning
confidence: 99%
“…In these studies, the volume and direction of the ellipsoid searching area were determined by a principal component analysis (PCA) method. However, the study areas of all above research were relatively flat with an elevation change less than 20 m. Zhang et al [18] demonstrated the relation between the signal-to-noise ratio (SNR) and several influential factors, including beam type, data collection time, and topography. As the slope increases, the SNR decreases sharply, and the same pattern applies for the sun presence and the SNR as well [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the study areas of all above research were relatively flat with an elevation change less than 20 m. Zhang et al [18] demonstrated the relation between the signal-to-noise ratio (SNR) and several influential factors, including beam type, data collection time, and topography. As the slope increases, the SNR decreases sharply, and the same pattern applies for the sun presence and the SNR as well [18]. Such situations become worse for the weak beam due to a further decrease on the SNR caused by a lower transmit energy [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The noise arises from several sources, including the laser pulse being scattered by the atmosphere, the solar background noise effects, and the detector dark noise. In our study, the main noise source is associated with photons that are scattered by particles in the water column [22]. Based on this first clustering, photons from the seabed were identified and corrected for the refraction effect occurring at the air-water interface.…”
Section: Introductionmentioning
confidence: 99%